Zinc-air battery air cathode electrocatalyst
By preparing high porosity manganese oxide nanoparticles supported nitrogen-doped carbon electrocatalyst (MnO/NC), the problem of low cathode oxidation and reduction reaction efficiency of zinc air battery is solved, and the efficient, stable and low-cost characteristics of zinc air battery cathode are achieved.
Patent Information
- Application Number
- CN202411569259.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-03-14
AI Technical Summary
The cathode oxidation and reduction reaction efficiency of zinc air batteries is low, resulting in low efficiency and short life. The existing precious metal catalysts are poorly stable and costly, making it difficult to apply on a large scale.
By increasing the porosity of the carbon material support, manganese ions are captured by the domain-limiting effect of the pore structure, a high-porosity manganese oxide nanoparticles supported nitrogen-doped carbon electrocatalyst (MnO/NC) is prepared as the cathode electrocatalyst for zinc-empty batteries.
The continuous and stable operation of the cathode of the zinc-empty battery has been achieved for more than 3300 hours, and has excellent oxygen reduction reaction activity and stability, reducing costs, and improving the power density and charging and discharge stability of the battery.
Smart Images

Figure CN119627131A_ABST
Abstract
Description
Technical Field
[0001] The present invention designs a zinc-air battery cathode electrocatalyst with high efficiency, low cost and excellent stability, and particularly relates to a preparation method of a MnO / NC electrocatalyst and application in a zinc-air battery. Background Art
[0002] In recent years, with the increasing demand for non-renewable energy such as oil, natural gas, and coal, climate change, environmental pollution, and energy shortages have become increasingly serious. In order to reduce dependence on non-renewable energy, the development and utilization of new energy sources, such as solar energy, wind energy, and hydropower, has attracted increasing attention. Due to the intermittent nature of these new energy sources, energy storage has become the key. Zinc-air batteries have the advantages of low cost (zinc and air are widely present in nature), environmental friendliness, high theoretical energy density (1086Wh kg −1 ), repeated charge and discharge, and high reliability, and have been vigorously promoted and studied. However, due to the slow redox reaction (ORR / OER) of the cathode, it has low efficiency and short life. At present, the most widely used materials on the market are precious metal Pt-based and Ru / Ir-based materials, corresponding to ORR and OER reactions respectively. Although these two catalysts have excellent performance, their shortcomings are also obvious, such as poor stability, high cost, single performance, and are not conducive to large-scale application. Therefore, the development of a non-precious metal catalyst with high efficiency, low cost and good stability is the core content of zinc-air battery research.
[0003] At present, non-precious metal catalysts mainly include transition metal-based catalysts (metal oxides, metal nitrides and alloys), carbon-based materials (one-dimensional carbon nanotubes, two-dimensional graphene nanosheets, three-dimensional porous carbon) and hybrids (metal-carbon hybrids and metal-nitrogen-carbon (MNC) materials). The above types of non-precious metal catalysts have achieved certain research results. Among them, manganese-based electrocatalysts not only have good oxygen reduction activity, but also the introduction of manganese can significantly improve the graphitization degree of carbon materials during high-temperature carbonization, thereby improving the stability of the catalyst. However, manganese-based electrocatalysts also face many problems in synthesis and preparation, especially in the precursor preparation and high-temperature carbonization process, they are very easy to agglomerate, resulting in insufficient catalytic active sites and poor catalyst activity. Summary of the invention
[0004] In response to the above technical problems, this patent improves the porosity of the carbon material carrier and uses the confinement effect of the pore structure to capture manganese ions in the adsorbed solution to prepare a high-porosity manganese oxide nanoparticle-loaded nitrogen-doped carbon electrocatalyst (MnO / NC). The catalyst has a rich pore structure, excellent ORR activity and stability. As the air cathode of a zinc-air battery, it can work stably for more than 3300 hours and has potential application value. The purpose of the present invention is to provide a MnO / NC electrocatalyst with excellent stability.
[0005] A MnO / NC electrocatalyst, wherein the MnO / NC electrocatalyst comprises characteristic peaks at 26°, 35°, 40°, 43° and 59° in an XRD spectrum.
[0006] MnO nanoparticles are uniformly dispersed on the nitrogen-doped carbon support with a size of 10-30 nm; the specific surface area of the sample is 1500-2000 m 2 g -1 , pore volume is 1.0-1.5 cm 3 g -1 .
[0007] Another object of the present invention is to provide a method for preparing a MnO / NC electrocatalyst, comprising the following steps: Step 1: dissolving MnCl2·4H2O in an alcohol solution, adding nitrogen-doped carbon powder supported by Zn grains to obtain a dispersion; Step 2: Stir the dispersion obtained in step 1 in a water bath at 30-35 °C for 10-12 h, evaporate the solvent at 60-80 °C, and dry to obtain Zn / NC@MnCl2 powder; Step 3: The Zn / NC@MnCl2 powder is pyrolyzed at high temperature to obtain the MnO / NC electrocatalyst. In the step 1, the alcohol solution is a C1-C5 alcohol solution.
[0008] The nitrogen-doped carbon powder loaded with Zn crystals is a product of sealed pyrolysis of zinc-based imidazole framework (ZIF-8) under an inert atmosphere.
[0009] In step 1, the mass ratio of MnCl2·4H2O to the nitrogen-doped carbon powder supported by Zn grains is 1:80-1:5.
[0010] In step 3, during the high-temperature pyrolysis process, the temperature is raised to 900-1000°C at 5-10°C / min in a high-purity Ar atmosphere for high-temperature pyrolysis for 1-2h.
[0011] Another object of the present invention is to provide an air cathode of a zinc-air battery, comprising the catalyst prepared by the method.
[0012] Another object of the present invention is to provide a quasi-solid-state zinc-air battery, wherein the quasi-solid-state zinc-air battery is a catalyst prepared by the method.
[0013] Another object of the present invention is to provide a liquid zinc-air battery, wherein the liquid zinc-air battery is a catalyst prepared by the method.
[0014] The MnO / NC electrocatalyst and preparation method involved in the present invention have the following significant features: (1) Rich pore structure, with a specific surface area of 1984 m 2 g -1 , the pore volume is 1.4 cm 3 g -1 ; (2) MnO is a nanoparticle with a size of only ~20 nm; (3) Excellent ORR activity: the oxygen reduction half-wave potential is 0.89 V vs. RHE; excellent stability: the current retention rate is more than 90% after working at a constant potential of 0.5 V vs. RHE for 5 h. As the air cathode of zinc-air batteries, it has achieved high power density (liquid: 220 mW cm -2 ; Quasi-solid state: 507 mW cm -2 ) and excellent charge and discharge stability (liquid battery at 10mAcm -2 The battery can be stably charged and discharged for more than 3000 h at a constant current density. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 XRD patterns of samples prepared in Examples 1, 2 and 3.
[0016] Figure 2 TEM image of the sample prepared in Example 1.
[0017] Figure 3 BET test results of the samples prepared in Example 1.
[0018] Figure 4 LSV curves of oxygen reduction reactions of samples prepared in Examples 1, 2, 3, and 4.
[0019] Figure 5 Chronoamperometric curve of oxygen reduction reaction between the sample prepared in Example 1 and Pt / C.
[0020] Figure 6 Discharge curve and power density curve of the quasi-solid-state battery assembled with the sample prepared in Example 1, Pt / C and RuO2.
[0021] Figure 7Discharge curve and power density curve of the liquid battery assembled with the sample prepared in Example 1, Pt / C and RuO2.
[0022] Figure 8 The sample prepared in Example 1 was used as the air cathode of the quasi-solid-state battery with Pt / C and RuO2 at a current density of 2 mA cm -2 Constant current cycle charge and discharge curve.
[0023] Fig. 9 The sample prepared in Example 1 was used as the air cathode of liquid zinc-air battery with Pt / C and RuO2 at a current density of 10 mA cm -2 Constant current cycle charge and discharge curve.
[0024] Fig.10 LSV curves of oxygen reduction reactions of samples prepared in Examples 5, 6 and 7. DETAILED DESCRIPTION
[0025] Example 1 Step 1: Take 25 mg of MnCl2·4H2O and dissolve it in 20 mL of methanol, add 400 mg of Zn grain-supported nitrogen-doped carbon powder (zinc-based imidazole framework (ZIF-8) precursor) and seal it under Ar inert atmosphere, pyrolyze it at 600 °C for 2 h, and evenly disperse it; Step 2: After the dispersion was stirred in a water bath at 35 °C for 12 h, the solvent was evaporated at 60 °C and dried to obtain Zn / NC@MnCl2 powder; Step 3: Spread the Zn / NC@MnCl2 powder in a corundum boat, place it in the center of a tube furnace, and heat it to 1000 °C at 10 °C / min in a high-purity Ar atmosphere for 1 h to obtain MnO / NC-1.
[0026] Figure 1 MnO / NC-1 is the XRD spectrum of the catalyst prepared in this example. The diffraction peaks at 26° and 43° correspond to the (002) and (101) crystal planes of graphitized carbon, and the sharp diffraction peaks at around 35°, 40°, and 59° correspond to the (111) (200) (220) crystal planes of MnO, indicating that the MnO / NC-1 sample is composed of MnO and nitrogen-doped graphitized carbon. TEM test was performed on the MnO / NC-1 catalyst, as shown in FIG. Figure 2 As shown in the figure, since the nitrogen-doped carbon supported by Zn grains comes from the sealed pyrolysis ZIF-8, the obtained MnO / NC-1 basically retains the rhombic dodecahedron morphology of ZIF-8 and has abundant pores inside. MnO nanoparticles are uniformly dispersed on the nitrogen-doped carbon support, with a size of about 20 nm. To further verify its excellent pore structure, the sample was subjected to BET test (such as Figure 3), the specific surface area of the sample was measured to be 1984.4 m 2 g -1 , the pore volume is 1.4 cm 3 g -1 The rich pore structure captures and confines manganese, making the MnO nanoparticles evenly dispersed.
[0027] The sample of this example was prepared into a slurry and dropped onto a rotating disk electrode, and its ORR performance was tested in an O2-saturated 0.1 M KOH solution. Figure 4 The ORR LSV curve of MnO / NC-1 is shown in the figure. It can be seen that at 1600 rpm, its half-wave potential is 0.89 V vs. RHE and the limiting current density is 5.8 mA cm -2 , showing excellent ORR performance. Figure 5 Figure 2 is the chronoamperometric curve of the oxygen reduction reaction of MnO / NC-1. After working at a constant potential of 0.5 V vs. RHE for 2 h, the current retention rate of MnO / NC-1 is 96%, and the current retention rate after 5 h is 91%. However, the current retention rate of Pt / C is only 84% after 2 h, indicating the excellent stability of MnO / NC-1.
[0028] The catalyst was evenly drop-coated on hydrophobic HCP120 carbon paper as the air cathode, the polished zinc plate as the anode, and the PANa hydrogel film as the electrolyte to assemble a quasi-solid-state zinc-air battery. Figure 6 The discharge curve and power density curve of the quasi-solid-state zinc-air battery assembled with MnO / NC-1 and Pt / C+RuO2 as air cathode. It can be seen from the figure that the power density of the MnO / NC-1 quasi-solid-state battery is as high as 507 mW cm -2 , which is much higher than the 226 mW cm of Pt / C+RuO2 battery. -2 .
[0029] The catalyst was evenly drop-coated on hydrophobic HCP120 carbon paper as the air cathode, a polished zinc plate was used as the anode, and a KOH solution containing 0.2 M Zn(OAc)2·2H2O was used as the electrolyte to assemble a liquid zinc-air battery. Figure 7 The discharge curve and power density curve of the liquid zinc-air battery assembled with MnO / NC-1 and Pt / C+RuO2 as air cathode. The power density of the MnO / NC-1 quasi-solid-state battery is 220 mW cm -2 , which is higher than the 140 mW cm of Pt / C+RuO2 battery. -2 , indicating that MnO / NC-1 has excellent battery performance as an air cathode. The quasi-solid-state battery assembled with MnO / NC-1 was tested at 2 mA cm -2Cyclic charge and discharge under constant current density can work stably for 52 h ( Figure 8 ), which has better stability than the quasi-solid-state battery assembled by Pt / C+RuO2 (~ 20 h). Fig. 9 As shown, the liquid battery assembled with MnO / NC-1 was -2 The battery was cyclically charged and discharged under a constant current density and there was still no obvious attenuation after stable operation for 3300 h, which was significantly better than the liquid battery assembled with Pt / C+RuO2 (300 h). This proves the excellent stability of the MnO / NC-1 electrocatalyst in zinc-air batteries.
[0030] Embodiment 2: Step 1: Take 50 mg of MnCl2·4H2O and dissolve it in 20 mL of methanol, add 400 mg of Zn grain-loaded nitrogen-doped carbon powder and evenly disperse it; Step 2: After the dispersion was stirred in a water bath at 35 °C for 12 h, the solvent was evaporated at 60 °C and dried to obtain Zn / NC@MnCl2 powder; Step 3: Spread the Zn / NC@MnCl2 powder in a corundum boat, place it in the center of a tube furnace, and heat it to 1000 °C at 10 °C / min in a high-purity Ar atmosphere for 1 h to obtain MnO / NC-2.
[0031] Figure 1 MnO / NC-2 is the XRD pattern of the catalyst prepared in this example. The diffraction peaks at 26° and 43° correspond to the (002) and (101) crystal planes of graphitized carbon, and the sharp diffraction peaks at around 35°, 40°, and 59° correspond to the (111) (200) (220) crystal planes of MnO, indicating that the MnO / NC-2 sample is also composed of MnO and nitrogen-doped graphitized carbon. The sample of this example was prepared into a slurry, dropped on a rotating disk electrode, and its ORR performance was tested in an O2-saturated 0.1 M KOH solution. Figure 4 The ORR LSV curve of MnO / NC-2 is shown in the figure. It can be seen that at 1600 rpm, its half-wave potential is 0.89 V vs. RHE and the limiting current density is 5.7 mA cm -2 , showing excellent ORR performance.
[0032] Embodiment 3: Step 1: Dissolve 75 mg of MnCl2·4H2O in 20 mL of methanol, add 400 mg of Zn grain-loaded nitrogen-doped carbon powder and disperse evenly; Step 2: After the dispersion was stirred in a water bath at 35 °C for 12 h, the solvent was evaporated at 60 °C and dried to obtain Zn / NC@MnCl2 powder; Step 3: Spread the Zn / NC@MnCl2 powder in a corundum boat, place it in the center of a tube furnace, and heat it to 1000 °C at 10 °C / min in a high-purity Ar atmosphere for 1 h to obtain MnO / NC-3.
[0033] Figure 1 MnO / NC-3 is the XRD pattern of the catalyst prepared in this example. The diffraction peaks at 26° and 43° correspond to the (002) and (101) crystal planes of graphitized carbon, and the sharp diffraction peaks at around 35°, 40°, and 59° correspond to the (111) (200) (220) crystal planes of MnO, indicating that the MnO / NC-3 sample is composed of MnO and nitrogen-doped graphitized carbon. The sample of this example was prepared into a slurry, dropped on a rotating disk electrode, and its ORR performance was tested in an O2-saturated 0.1 M KOH solution. Figure 4 The ORR LSV curve of MnO / NC-3 is shown in the figure. It can be seen that at 1600 rpm, its half-wave potential is 0.88 V vs. RHE and the limiting current density is 6.1 mA cm -2 , showing excellent ORR performance.
[0034] Embodiment 4: Step 1: Dissolve 12.5 mg of MnCl2·4H2O in 20 mL of methanol, add 400 mg of Zn grain-loaded nitrogen-doped carbon powder and disperse evenly; Step 2: After the dispersion was stirred in a water bath at 35 °C for 12 h, the solvent was evaporated at 60 °C and dried to obtain Zn / NC@MnCl2 powder; Step 3: Spread the Zn / NC@MnCl2 powder in a corundum boat, place it in the center of a tube furnace, and heat it to 1000 °C in a high-purity Ar atmosphere at 10 °C / min for 1 h to obtain MnO / NC-4. Prepare a slurry of the sample and drop it on a rotating disk electrode to test its ORR performance in an O2-saturated 0.1 M KOH solution. Figure 4 The ORR LSV curve of MnO / NC-4 is shown in the figure. It can be seen that at 1600 rpm, its half-wave potential is 0.88 V vs. RHE and the limiting current density is 6.1 mA cm -2 , showing excellent ORR performance.
[0035] Compared with Example 1, the experimental steps and other drug dosages are kept unchanged, and the mass of the added MnCl2·4H2O is reduced to 5 mg. The ORR LSV curve of MnO / NC-5 is as follows: Fig.10As shown in the figure, at 1600 rpm, its half-wave potential decreases to 0.86 V vs. RHE, and the limiting current density is 5.8 mA cm -2 , its ORR performance is obviously attenuated.
[0036] Compared with Example 1, the experimental steps and other drug dosages are kept unchanged, and the mass of the added MnCl2·4H2O is increased to 80 mg. The ORR LSV curve of MnO / NC-6 is as follows: Fig.10 As shown in the figure, at 1600 rpm, its half-wave potential decreases to 0.85 V vs. RHE, and the limiting current density is 5.4 mA cm -2 , the ORR performance is obviously attenuated.
[0037] Compared with Example 1, the experimental steps and other dosages of the drugs are kept unchanged, and the nitrogen-doped carbon powder loaded with Zn crystals added in step 1 is replaced with nitrogen-doped carbon powder. The ORR LSV curve of MnO / NC-7 obtained is as follows: Fig.10 As shown in the figure, at 1600 rpm, its half-wave potential decreases to 0.85 V vs. RHE, and the limiting current density is 5.5 mAcm -2 , the ORR performance is obviously attenuated.
Claims
1. A MnO / NC electrocatalyst, characterized in that: The MnO / NC electrocatalyst includes characteristic peaks at 26°, 35°, 40°, 43°, and 59° in the XRD spectrum.
2. The MnO / NC electrocatalyst according to claim 1, characterized in that MnO nanoparticles are uniformly dispersed on the nitrogen-doped carbon support with a size of 10-30 nm; the specific surface area of the sample is 1500-2000 m 2 g -1 , pore volume is 1.0-1.5 cm 3 g -1 .
3. The method for preparing the MnO / NC electrocatalyst according to claim 1 or 2, characterized in that: The steps include: Step 1: dissolving MnCl2·4H2O in an alcohol solution, adding nitrogen-doped carbon powder supported by Zn grains to obtain a dispersion; Step 2: Stir the dispersion obtained in step 1 in a water bath at 30-35 °C for 10-12 h, evaporate the solvent at 60-80 °C, and dry to obtain Zn / NC@MnCl2 powder; Step 3: The Zn / NC@MnCl2 powder is pyrolyzed at high temperature to obtain the MnO / NC electrocatalyst.
4. The method for preparing the MnO / NC electrocatalyst according to claim 3, characterized in that: In step 1, the alcohol solution is a C1-C5 alcohol solution.
5. The method for preparing the MnO / NC electrocatalyst according to claim 3, characterized in that: The nitrogen-doped carbon powder loaded with Zn crystal grains is a product of sealed pyrolysis of zinc-based imidazole framework ZIF-8 in an inert atmosphere.
6. The method for preparing the MnO / NC electrocatalyst according to claim 5, characterized in that: In step 1, the mass ratio of MnCl2·4H2O to the nitrogen-doped carbon powder supported by Zn grains is 1:80-1:
5.
7. The method for preparing the MnO / NC electrocatalyst according to claim 1, characterized in that: In step 3, during the high-temperature pyrolysis process, the temperature is raised to 900-1000°C at 5-10°C / min in a high-purity Ar atmosphere for high-temperature pyrolysis for 1-2h.
8. Zinc-air battery air cathode, characterized in that The air cathode of the zinc-air battery comprises the electrocatalyst according to claim 1 or 2 or a catalyst prepared by the method according to any one of claims 3-7.
9. A quasi-solid-state zinc-air battery, characterized in that: The quasi-solid-state zinc-air battery comprises the electrocatalyst according to claim 1 or 2 or a catalyst prepared by the method according to any one of claims 3-7.
10. Liquid zinc-air battery, characterized in that: The liquid zinc-air battery comprises the electrocatalyst according to claim 1 or 2 or a catalyst prepared by the method according to any one of claims 3-7.